THE FORMATION AND INFLUENCE OF THE MILITARY ARCHITECTURE IN OMAN DURING AL-YA'ARIBA PERIOD (1034-1162 AH/1624–1749 AD) - Naima Benkari (Journal of Islamic Architecture, 2021)
Despite its richness, the research corpus published about Islamic architecture presents some discontinuities in the knowledge of the architecture in the lands ruled by Muslims. Similarly, the dynamics of influence that might have operated between the "monumental" architecture in these lands and their popular architectures are insufficiently addressed. Moreover, the material culture related to the Islamic civilization is almost exclusively studied as a product that has stopped evolving. The architecture produced during Al-Ya'ariba (Al- Ya'rubi) Imamate (1624-1749) is an instance of these understudied topics in the history of Islamic architecture. This research argues that Al-Ya'rubi Imamate is not only an important chapter in the history of Oman, the Arabian Peninsula, Indian Ocean, and Eastern Africa, but also the architecture of this period has created the identity of Omani architecture as we know it today. Nonetheless, there is no architectural production in this era both in the major references and scientific publications of Islamic architecture in the 17th and 18th centuries. Through field research, comparative analysis, and literature review of the history of Omani architecture, especially in the 17th -18th centuries, this research examines the military architecture in Oman during Al-Ya'ariba Imamate including its reference, and its influence on other architectures. It is a contribution to the scientific endeavour to address this specific architectural typology from the perspective of its mechanism of (trans) formation and its continuity of forms until the contemporary architecture of Oman.